Inclusion of fish waste silage in broiler diets affects gut microflora, cecal short-chain fatty acids, digestive enzyme activity, nutrient digestibility, and excreta gas emission. (8th May 2019) - Shabani, A; Jazi, V; Ashayerizadeh, A; Barekatain, R
ABSTRACT: A study was conducted to determine the impacts of dietary inclusion of fish waste silage (FWS) substituting soybean meal (SBM) on the performance, gut microflora, cecal short-chain fatty acid, apparent ileal digestibility (AID), digestive enzyme activity, and excreta noxious gas emission in broiler chickens. A total of 720-day-old male broilers (Cobb 500) were randomly allocated to 3 dietary treatments with 12 replicates each accommodating 20 birds for 42 d. Birds received diets as follows: a corn-SBM-based diet (CON) and 2 diets that replaced SBM with FWS at 60 g/kg (FWS60 ) and 120 g/kg (FWS120 ). During the entire period, replacing SBM with FWS60 and FWS120 increased body weight gain and decreased feed conversion ratio ( P < 0.05). The lowest pH values in the crop, proventriculus, duodenum, ileum, and ceca were observed in birds fed diets containing FWS60 and FWS120 ( P < 0.05). Likewise, birds fed FWS60 and FWS120 had lower numbers of coliform and E. coli and higher Bifidobacterium and Lactobacillus count in the ceca than those fed CON ( P < 0.05). Feeding FWS60 and FWS120 diets increased cecal butyrate and lactic acid contents ( P < 0.05). Birds fed FWS120 diets had greater intestinal amylase and protease activity than birds fed CON ( P < 0.05); however, no significant differences were recorded between the treatment groups for digestive enzymes activity in the pancreas. The use of both levels of FWS in broiler diet increased AID of crude protein and ether extract ( P < 0.05). The lowest excreta ammonia concentration was recorded in birds fed FWS120 diet ( P < 0.05). In conclusion, the inclusion of FWS in broiler diets could improve the performance by enhancing gut function, derived from the improved digestive enzyme activity and nutrient digestibility, as well as by elevating the population of beneficial bacteria and short-chain fatty acid contents. Therefore, the biological silage can be considered as a promising option for recycling and recovery of fish wastes and effectively be used in broiler diets.